Process Approach in the Management of the Organization: Theoretical Aspect - A. Krylova (Евразийская интеграция: экономика, право, политика, 2019)
Due to the major changes in global economy, the problem of selection and adaptation of approaches in management of organizations which is able to respond to these changes is particularly important. This article presents the basic theoretical principles of the process approach to organization management. It contains the conclusion about the need to switch from the functional management to a process management.